Analisis Literatur Mengenai Aplikasi Termodinamika Dalam Mesin Pembakaran - Zendrato, Septriani (CV. SINAR HOWUHOWU, 2025)
Co-firing of coal and biomass in an existing coal fired power plant is being considered as a viable alternative to transition from non-renewable-to-renewable energy utilization. In this regard, various researches have been conducted in the last twenty years, in most of which the general conclusion is that the boiler efficiency decreases with respect to increasing biomass percentage in co-firing, nonetheless, additional study is deemed to be required, especially for waste biomass which are abundantly available in Indonesia. The waste biomass to be employed in this study are palm empty fruit bunch (EFB), rice husk, and wood pellet produced from sawdust. Co-firing combustion thermodynamic characteristics which are to be deployed in this study are air-to-fuel ratio (AFR), combustion CO2 emission, and adiabatic flame temperature. An open source CoolProp of thermodynamics properties formulations were implemented in order to evaluate thermodynamic properties of corresponding materials involved in this study. The results of the study show that AFR decreases with increasing biomass composition in the fuel, where the AFR rate of change per percent of biomassa are -0.018, -0.0406, and -0.026 for blend of coal-EFB, coal-rice husk, and coalwood, respectively. As to the AFR characteristic, the emission of carbon dioxide is decreasing with